A família Asteraceae na Serra dos Pireneus, Goiás, Brasil - Pacheco, Rodrigo Andrade (2014)
CHAPTER I: In Brazil the tribe Eupatorieae Cass. (Asteraceae) is one of the richest in diversity, along with Vernonieae and Heliantheae, with 606 species in 84 genera. For the state of Goiás, surveys for family at Chapada dos Veadeiros, and Serra Dourada , indicate 31spp./12gêneros, and 22spp./12gêneros respectively. This paper aims to survey and systematic treatment of the tribe to the region of Serra dos Pireneus. This area is located between the towns of Pirenópolis, Corumbá de Goiás and Cocalzinho de Goiás, where fields and savannas predominate rock rock. Specimens were collected in six expeditions over the years 2012 and 2013, or arising out of eleven visited herbaria. The tribe is represented by 50spp. 18 genera, demonstrating the wealth of the tribe in the area. Were collected and studied specimens in herbaria species as Goyazianthus tetrastichus (B.L.Rob.) R.M.King & H.Rob., Leptoclinium trichotomum Benth. ex Baker and Planaltoa salviifolia Taub. typical of Goiás, while other species have expanded their geographical distributions for the state of Goiás, as Chromolaena myriocephala (Gardner) R.M.King & H.Rob. and Mikania lasiandrae DC. In this paper an identification key, taxonomic description and comments for each species are presented. CHAPTER II: This paper presents a list of species of Asteraceae from Serra dos Pireneus, state of Goiás, and an analysis of the similarity between 15 Brazilian areas with predominantly rocky fields, rocky savannas and/or highlands. All species of the 15 areas compared were arranged in a table of absence and presence, and using the Jaccard index, the similarity between them was calculated. For the region of Serra dos Pireneus were recorded 201 species belonging to 71 genera and 17 tribes. The highest species diversity is found in the tribes Vernonieae (62spp./18 genera), Eupatorieae (50spp./18 genera) and Heliantheae (21spp./8 genera), and in the genera Lessingianthus (24spp.), Chromolaena (13spp.), Calea (11spp.), Baccharis and Mikania (10spp. each). The region of Serra dos Pireneus has greater floristic similarity with the Serra Dourada (J=0.3065), Chapada dos Veadeiros (J=0.25) and Serra da Canastra (P=0.2386), and the lowest similarity with the Serra dos Órgãos (J=0.0308). There was a significant correlation in relation to floristic similarity and geographical distance between the areas analyzed (r=0.612, p=< 0.01). Through cluster analysis using UPGMA, it is clear that the matrix of dominant vegetation and geo-climatic characteristics, as well as geographic distance, can explain local floristic composition.